Evaluation of Genotoxicity of Sediments from the Sado-River Estuary Using Solvent Extractions of Diferent Polarities - Vicente, Ana Margarida (2013)
Located in the western coast of Portugal, our case study, the river Sado Estuary, is affected by various sources of pollution, such as heavy-industry, urbanism, mining, agriculture and maritime traffic. Recent studies showed that sediment samples were contaminated with a mixture of different groups of contaminants related to the different anthropogenic pressures along the estuary. The present study aims to assess the cytotoxic and genotoxic potential of these sediments following a fractioning method, in order to elucidate whether their toxicity can be attributed to a particular group of contaminants, or is rather the result of the complex interaction of contaminants. Sediment samples were collected from four distinct and contaminated sites of the Sado Estuary: sites C and P from the urban/industrial area and sites E and A from the riverine/agriculture area. Organic and inorganic contaminants were extracted with solvents of increasing polarity n-hexane < dichloromethane < methanol and a mixture (DCM:methanol), and recovered in DMSO. Cytotoxicity and genotoxicity were evaluated through the neutral red and comet (coupled with FPG) assays, respectively, in HepG2 cells. Cells were exposed for 48h to concentrations of each extract ranging from 1 to 200 mg SEQ/ml. Cytotoxicity was only observed for extracts PDCM/met, EDCM/met and Pmet. Sediment sample C failed to induce genotoxicity. A significant increase in the level of DNA damage was observed for sub-cytotoxic concentrations of PDCM/met, EDCM/met and Pmet. DNA damage was accentuated following treatment with FPG, suggesting oxidative DNA damage, mainly for DCM/met extractions of all samples except C, as well as Phex and Pmet. Complex toxicant mixtures are present in estuarine sediments which often makes the association between surveyed contaminants and toxicity difficult to establish. In this study, genotoxic effects were observed in extracts obtained with the mixture of solvents (DCM:met). Nevertheless, when different extractions were performed with solvents of different polarities, the effects of the different fractions were mainly diluted, or more weakly expressed, suggesting that the interaction between contaminants, and not a set of particular contaminants, might be responsible for the observed effects. Also, we suggest that oxidative DNA damage, revealed by the FPG enzyme, might be a common effect of the exposure to these environmental contaminants. Together with contamination analysis, these results are expected to disclose the genotoxic potential of sediment sample extracts in a human cell line, in order to derive a potential risk to human health.